PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK KIMIA BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI SENYAWA HIDROKARBON KELAS XII SMA - Sari, Diah Kartika; Dwinadia, Yara (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2025)
This research aimed to develop Lembar Kerja Peserta Didik (LKPD) is known for Problem-Based Student Worksheets with the topic of Hydrocarbon Compounds in SMA Negeri 1 Indralaya which is valid, practical and effectively with learning materials in the classroom. The development of the LKPD is expected to increase students’ involvement in the learning process and facilitate the understanding of concepts are taught deeply and structurally. The research method is used Development Research with the Rowntree Model and Tessmer Formative Evaluation. The subject of this research is the students of the twelve graders in SMA Negeri 1 Indralaya. The twelfth grade students of SMA Negeri 1 Indralaya. The validity result in the aspect of material is 0.94 (high), the aspect of pedagogical is 0,94 (high), and the aspect of design is 0.96 (high). Meanwhile, based on the practicality result of the LKPD was obtained One-to-One is 89.57% (very practical) and Small Group is 90.82% (very practical). The LKPD has been effective with an N-Gain value is 75.88% (high). This research is concluded that the LKPD has been developed can be used as a tool for learning aid.